The Effect of Mulching Technology to Enhance the Diversity of Soil Macroinvertebrates in Sengon-based Agroforestry Systems - SUGIYARTO SUGIYARTO (Society for Indonesian Biodiversity, 2009)
Soil macroinvertebrate are strongly influenced by environmental factors. The change of agronomic technology may affect their role in maintaining soil fertility and crop production. The aim of this study was to know the effect of technology of mulching to enhance diversity of soil macroinvertebrate in sengon-based agroforestry system. Field experiment was arranged in randomized block design with treatment i.e. with and without organic matter mulching. Sweet potato used as tested intercrop. Collection of soil macroinvertebrate was carried out using a hand sorting and pit-fall trap methods. Result of the study showed that application of maize residue as mulch enhanced diversity index of surface and deep soil macroinvertebrate, i.e: 0.215 and 0.214 (by 44% and 73% respectively compared no mulching). Organic mulching technology can support diversity of beneficial soil macroinvertebrates.Key words: agroforestry, soil macroinvertebrates, sengon (Paraserianthes falcataria), mulching.